Repeated Sprint Performances among Girls and Women: 少女與婦女的無氧能力 - CHIA, Michael (Asian Journal of Physical Education & Recreation, 2001)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. The aim of the study was to compare between girls and women, the recovery of Wingate Anaerobic Test (WAnT) power after two prior sprints of 15-seconds’ duration with a short active recovery interval in-between the sprints. Participants with written informed consent were 19 girls (age: 13.6±1.0yrs; body mass: 51.2±7.6kg & stature: 1.59±0.06m) and 21 women (age: 25.1±2.7yrs; body mass: 57.9±7.7kg & stature: 1.61±0.05m). Lower limb muscle mass was determined using a Dual-energy X-ray Absorptiometric (DXA) procedure. Following a standardized warm-up, each participant completed a series of three 15-second WAnTs, with each test separated by a 45-second active recovery interval. WAnT power variables were computed over 1-second time periods and were corrected for the inertia of the cycle ergometer (Monark 834E). Whole blood lactate concentrations (BL) were obtained immediately post warm-up and at three minutes after the completion of the third WAnT. Peak power (PP), expressed in watts per lower limb muscle mass (W. kg -1LLMM) were significantly greater in women than in girls in the first 15s WAnT (46.1±10.9 vs 37.4±2.3W.kg -1LLMM, p<0.05). However mean power (MP) over the first test was not significantly different between the girls and women (33.8±2.1 vs 34.7±5.9W.kg -1LLMM, p>0.05). Girls were better able to replicate their power achieved in the first WAnT, in the third WAnT than women (mean of the differences ± standard deviation of the differences for PP: 84±47W vs 174±84W; MP: 81±45W vs 161+65W, p<0.05). Despite the better recovery in WAnT power in girls during the third 15s cycle sprint, BL taken at post- warm-up (2.5±0.5 vs. 1.9±0.5 mM.L-1, p >0.05), and at three minutes post exercise (9.2±1.2 vs. 8.4±1.3 mM.L-1, p >0.05) were not significantly different in girls and women. 本文以溫蓋特無氧功率試驗(Wingate Anaerobic Test, WAnT)為研究方法，重複測定了少女和婦女15秒的無氧功率，旨在比較少女與婦女之間的無氧能力極其恢復。受試對象為19名少女(年齡：13.6±1.0歲；體重：51.2±7.6公斤；身高：1.59±0.06米）和21名婦女（年齡:25.1±2.7歲；體重：57.9±7.7公斤；身高：1.61±0.05米）。以雙光能X光吸收儀(DXA)測定受試者下肢的瘦體重。在標準化的準備活動之後，受試者在自行車測功儀(Monark 834E)上完成3次15秒最快速度的踏車運動，各次運動之間以45秒的活動性休息為間隔。在準備活動後即刻和第三次運動試驗后3分鐘采血測定血乳酸濃度。在首次15秒WAnT測試中，婦女組的最高功率(46.1±10.9瓦．公斤下肢瘦體重-1)明顯高于少女組(37.4±2.3瓦．公升-1肢瘦體重-1，p<0.05)，而婦女組與少女組的平均功率無顯著性差異，分別為34.7±5.9瓦．公升-1肢瘦體重-1與33.8±2.1瓦．公升-1肢瘦體重-1 (p>0.05)。第三次15秒運動試驗中，少女組的無氧功率明顯地較婦女組接近第一次WAnT測試中所達到的功率(p<0.05), 最高功率均值差分別為84±47瓦與174±84瓦；平均功率均值差分別為81±45瓦與161±65瓦。雖然少女組在WAnT測試中顯示出較好的恢復能力，但無論是準備活動后還是第三次WAnT運動試驗后，少女組與婦女組血乳酸濃度的相差無顯著性意義(P>0.05)，分別為2.5±0.5毫克分子．升-1與1.9±0.5毫克分子．升-1及9.2±1.2毫克分子．升-1與8.4±1.3毫克分子．升-1。